Oligonucleotide dendrimers: stable nano-structures. - Shchepinov, MS; Mir, K; Elder, J; Frank-Kamenetskii, MD; Southern, E (1999)
DNA dendrimers with two, three, six, nine or 27 arms were reassociated as complementary pairs in solution or with an array of complementary oligonucleotides on a solid support. In all cases, duplex stabilities were greater than those of unbranched molecules of equal length. A theoretical treatment for the process of dissociation of dendrimers explains the major properties of the complexes. The favourable features of DNA dendrimers-their enhanced stability and the simple predictability of their association behaviour-makes them promising as building blocks for the 'bottom up' approach to nano-assembly. These features also suggest applications in oligonucleotide array/DNA chip technology when higher hybridisation temperatures are required, for example, to melt secon-dary structure in the target.